Acceptability, feasibility, and individual preferences of blood-based HIV self-testing in a population-based sample of adolescents in Kisangani, Democratic Republic of the Congo - Tonen-Wolyec, Serge (PLoS One, 2019)
BACKGROUND: Adolescents living in sub-Saharan Africa constitute a vulnerable population at significant risk of HIV infection. This study aims to evaluate the acceptability, feasibility, and accuracy of home-based, supervised HIV self-testing (HIVST) as well as their predictors among adolescents living in Kisangani, Democratic Republic of the Congo (DRC). METHODS: A cross-sectional, door-to-door survey using a blood-based HIV self-test and a peer-based supervised HIVST approach was conducted from July to August 2018 in Kisangani, DRC. The acceptability and feasibility of HIVST were assessed among adolescents’ consenting to use and interpret HIV self-test. The accuracy of HIVST was estimated by the sensibility and specificity of adolescent-interpreted HIV self-test. Factors associated with acceptability and feasibility of HIVST were analyzed with logistic regression. RESULTS: A total of 628 adolescents (including 369 [58.8%] females) aged between 15 and 19 years were enrolled. Acceptability of HIVST was high (95.1%); 96.1% of participants correctly used the self-test, and 65.2% asked for verbal instructions. The majority of adolescents (93.5%) correctly interpreted their self-test results. The Cohen’s κ coefficient between the results read by adolescents and by supervisors was 0.62. The correct interpretation decreased significantly when adolescents had no formal education or attended primary school as compared to those currently attending university (37.0% versus 100%; adjusted OR: 0.01 [95% CI: 0.004–0.03]). In the hands of adolescents at home, the sensitivity of the Exacto Test HIV Self-test was estimated at 100%, while its specificity was 96.0%. The majority of participants (68.0%) affirmed that post-test counseling was essential, and that face-to-face counseling (78.9%) was greatly preferred. CONCLUSIONS: Home-based, supervised HIVST using a blood-based self-test and peer-based approach can be used with a high degree of acceptability and feasibility by adolescents living in Kisangani, DRC. Misinterpretation of test results is challenging to obtaining good feasibility of HIVST among adolescents with poor educational level. Face-to-face post-test counseling seems to be preferred among Kisangani’s adolescents.